Reasons of Open Defecation Behavior in Rural Households of Bhopal, Madhya Pradesh, India - Namdev, Garima; Narkhede, Vinod (National Journal of Community Medicine, 2020)
Background: According to World health organization (WHO), open defecation (OD) is a major public health concern in India both in rural and urban counterparts. Therefore, Government decided to eliminate open defecation (OD) by 2019 with the introduction of Swachh Bharat Mission. But, still, many individuals found to choose to defecate in open fields. The study was conducted to find out the prevalence of open defecation and its reasons. Material and methods: The present cross sectional, descriptive study was carried out across villages coming under rural field practice area for one year. Total five villages were randomly selected consisting of 1000 population approximately. Data was collected using pre designed questionnaire and analyzed using SPSS 23.0. Result: Out of total 1000 study subjects, 27.7% study subjects opt for defecation practices. Out of them, 76.5% opt due to their habits. Next reason (57%) came out was feeling comfortable followed by unawareness (36.4%) and lack of water (34%). Conclusion – The present study concluded prevalence of open defecation 27.7%. Due to their habits, feeling comfortable, unawareness and lack of adequate water in study area were major factors contributing persistence of open defecation.